2019
DOI: 10.1002/mde.3097
|View full text |Cite
|
Sign up to set email alerts
|

The bright side and dark side of trust: The mediating effect of franchisor trust on performance

Abstract: Previous literature has not examined the dual role of trust in franchise relationships. We extend the franchise and relational governance literature by showing that trust has both a “bright side” and a “dark side” in franchisor–franchisee relationships. Based on transaction cost and knowledge‐based reasoning, we argue that intangible knowledge assets and environmental uncertainty have an indirect effect on performance via trust, due to its relational risk and knowledge exchange effect. Using data from the fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
2
0
1
Order By: Relevance
“…In a related study, Brown and Dev (1997) identified three levels of partnership qualities within franchise chainslow, medium and highand showed that performance was higher for systems with medium or high partnership qualities. More recently, studies observed that standardization requirements and perceived trust in the franchisor affected franchisee sales and service performance (Minarikova et al, 2019;Chiou and Droge, 2015). Mignonac et al (2015) showed a positive relationship between franchisees' affective commitment and franchise system success.…”
Section: Franchise Relationshipmentioning
confidence: 99%
“…In a related study, Brown and Dev (1997) identified three levels of partnership qualities within franchise chainslow, medium and highand showed that performance was higher for systems with medium or high partnership qualities. More recently, studies observed that standardization requirements and perceived trust in the franchisor affected franchisee sales and service performance (Minarikova et al, 2019;Chiou and Droge, 2015). Mignonac et al (2015) showed a positive relationship between franchisees' affective commitment and franchise system success.…”
Section: Franchise Relationshipmentioning
confidence: 99%
“…Asimismo, los franquiciadores más antiguos ingresan a los mercados internacionales, tienen una mayor capacidad para desarrollar nuevas capacidades que mejoran las relaciones franquiciador-franquiciado [9]. Para futuras investigaciones, los autores plantean como propuesta el examinar la relación de la confianza entre los activos específicos del sistema y el rendimiento, con medidas alternativas de activos intangibles específicos del sistema [26]. De igual manera, se propone concentrar las investigaciones tanto en franquicias privadas y las más pequeñas que se identifican como empresas familiares, con la intención de demostrar las diferencias significativas debido a las condiciones culturales, económicas y políticas del país de origen [8].…”
Section: Discusión a Las Tendencias Comerciales Que Influyen En La In...unclassified
“…It might be possible that certain nodes get (re)engaged with significant time-lags and as such remain dormant first or higher order elements of a network's service ecosystem due to the changing needs and preferences of the collaborative organization. However, the intermittent nature of interaction/cooperation with certain nodes becoming dormant for a sufficiently longer period of time, may lead to a decline of productivity attributable to organizational A c c e p t e d m a n u s c r i p t forgetting (de Holan & Phillips, 2004;Thompson, 2007), loss of network identities (Eklinder-Frick, Eriksson & Hallén, 2014) and strategic blindness as "hidden costs of trust" (Selnes & Sallis, 2003;Minarikova, Mumdziev, Griessmair & Windsperger, 2020). In essence, the efficacy of such collaborative networks for dynamic co-creation of value depends, to a reasonable extent, upon the perseverance of identities, quality of social embeddedness and the innovative generativity in their social capitals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%